Pelatihan Praktik Pengukuran Arah Kiblat Bagi Penyuluh Agama Islam KUA Kecamatan Air Hangat Kab. Kerinci - Darlius Darlius; Susi Susanti; Hannilfi Yusra (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The accuracy of the qibla direction is a fundamental aspect of performing valid prayers according to Islamic law. However, many Islamic religious counselors at the KUA still face difficulties in determining the qibla direction precisely and accurately. This community service research aims to enhance the competence of Islamic religious counselors at the Air Hangat Subdistrict KUA in Kerinci Regency in the practice of measuring the direction of the qibla through comprehensive training that combines the theory of astronomy and practical application using modern instruments. The community service method employed the ABCD approach (Attraction, Building, Commitment, Delivery), featuring theoretical sessions, hands-on measurement practice using a theodolite and qibla compass, and reflective discussions on measurement error tolerance. The results of the activity showed that 35 religious counselors experienced a significant improvement in their understanding of astronomical concepts and practical skills in measuring the direction of the qibla, with a post-training accuracy rate reaching 95%. Participants were able to calibrate the qibla directions of mosques in their work areas with a maximum deviation of 0°6'15